Unravelling the Dynamics of Border Crossing and Rural‐to‐Rural‐to‐Urban Mobility in the Northeastern Thai–Lao Borderlands. Issue 7 (October 2016) - Rungmanee, Soimart
Abstract: A considerable number of migration studies to date have focused on either internal or international migration. Such studies tend to highlight the economic inequality that underlies human mobility, and hold that migration proceeds according to the rural‐to‐urban divide, as well as between nation‐states. However, these approaches fail to describe how labour moves internally, internationally, and within and across sectors. This paper addresses this complexity by examining cross‐border migration that takes Lao migrants from agricultural to service sectors, from the hinterland of Laos to the borderlands of northeast Thailand, and from Laos to Bangkok and other urban centres in Thailand. By drawing upon case studies in a border village in northeast Thailand and in two villages in Lao People's Democratic Republic, this study shows that Lao migrants engage in rural‐to‐rural migration at different stages of their lives and reveals how internal migration in Thailand leads to emigration from Laos. Although a relatively high wage rate in Thailand plays a critical role in human mobility across the border, there are other determining factors that need to be considered, including the historical context of the movement between the sending and receiving areas, geographical proximity, and a shared linguistic and cultural background that supports cross‐border migration and which complicates migration patterns. Copyright © 2015 John Wiley & Sons, Ltd.